A Mild, Efficient and Reusable Solid Phosphotungestic Acid Catalyst Mediated Synthesis of Benzoxazole Derivatives: A Grinding Approach - R. Patil, Mahadeo; Yelamaggad, Aditya; S. Keri, Rangappa (Letters in Organic Chemistry, 2016)
Background: The development of efficient methodologies for the preparation of benzoxazole and its derivatives has gained a lot of importance in current research. There are many methods are reported for the synthesis of benzoxazoles includes condensation of 2-aminophenol with carboxylic acid. Traditional methods also have several side reactions, non renewable oxidative reagents and solvents which negatively affect the environmentally and eco-friendly nature of the reaction. We have developed PTA catalyzed synthesis of 2-arylbenzoxazole from 2-aminophenols with different aromatic aldehydes using a grinding strategy in excellent yield. Methods: The synthesis of benzoxazoles in high yields by using silica supported PTA/PTA as solid acid catalyst at room temperature using grinding method. Results: Aromatic aldehydes which have electron donating or electron withdrawing groups were also investigated and as expected it gives good to excellent yield of products, it can be seen that electron donating and electron withdrawing groups does not show any difference on their action yields. Conclusion: We have developed PTA catalyzed synthesis of 2-arylbenzoxazole from 2-aminophenols with different aromatic aldehydes using a grinding strategy in excellent yield. The use of this reusable catalyst under solvent-free conditions has made this protocol practical, environmentally friendly and economically attractive. The simple work-up procedure, the short reaction times the mild reaction conditions, the high yields of products and the non-toxicity of the catalyst are other advantages of the present method. This protocol approaches combines the advantages of both focused library synthesis and diversity oriented synthesis because of the simplification of reaction protocol that we have been developed.
Keywords: Synthesis